The Effect of Current Ratio and Quick Ratio on Syariah Stock Prices at PT. Aneka Tambang Tbk Listed on Jakarta Islamic Index (JII) in The Period 2018-2023 - Fitriyani Fitriyani; Fanlia Prima Jaya; Rezti Rezti (PT. Hanken Sukses Jaya, 2025)
This study aims to analyze the effect of Current Ratio and Quick Ratio on the sharia stock price of PT Aneka Tambang Tbk listed on the Jakarta Islamic Index (JII) during the 2018-2023 period. Current Ratio is calculated by comparing current assets with current liabilities, while Quick Ratio is calculated by subtracting inventory from current assets and then comparing it with current liabilities. The price of sharia stocks is measured based on the equity value divided by the number of shares outstanding. The population of this study includes all quarterly financial reports of PT Aneka Tambang Tbk listed on the JII during the 2018-2023 period, with a total of 24 reports. Because the population is less than 100, the entire population was taken as a research sample using a saturated sampling technique. The analysis method used is linear regression with the help of SPSS software. The results of the study show that the Current Ratio partially has a significant effect on the price of sharia stocks. Likewise, the Quick Ratio also shows a significant partial effect on the price of sharia stocks. In addition, the Current Ratio and Quick Ratio simultaneously have a significant effect on the sharia stock price of PT Aneka Tambang Tbk listed on the Jakarta Islamic Index during the period studied.